1985
DOI: 10.2466/pms.1985.61.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Personality Factors in Responsivity to Pain

Abstract: This study investigated the relationship between measured levels of masculinity-femininity, social desirability, and responsivity to pain in men and women. The literature suggests that the two personality variables might provide an explanation for the common findings of higher pain thresholds and tolerances in men than in women. A significant interaction was found between masculinity-femininity and sex for pain thresholds. Analysis of this interaction indicated that for men, but not women, there was a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
1
4

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(102 citation statements)
references
References 14 publications
7
90
1
4
Order By: Relevance
“…In this study, we found an insignificant inverse relationship between baseline pulse and pain sensitivity as indicated by pain threshold and pain tolerance. This relation was also found by Cynthia d. Myers et al (7) , and Otto and Dougher in their studies (9) . …”
Section: Discussionsupporting
confidence: 69%
“…In this study, we found an insignificant inverse relationship between baseline pulse and pain sensitivity as indicated by pain threshold and pain tolerance. This relation was also found by Cynthia d. Myers et al (7) , and Otto and Dougher in their studies (9) . …”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, cultural factors may be involved, such as the education of males to have a stoic attitude and to underreport pain. 20 Gender differences in pain perception are thought to be infl uenced by a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Fillingim et al 14 suggested that pain responses may be more clinically relevant for women than for men. Other factors, such as sex role expectancies 15 and anxiety, 16 may also modulate differences in pain between men and women.…”
Section: Discussionmentioning
confidence: 99%